PENGEMBANGAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL PADA MASYARAKAT MINORITAS ( Studi atas Kearifan Lokal Masyarakat Adat Suku Baduy Banten) - Hasanah, Aan (Universitas Islam Negeri Raden Intan Lampung, 2012)
The nation’s character is built from the core ethical values derived from the values of religion, philosophy and culture of the State. The values derived from national cultures are in great quantities and of highly diverse and contain lofty values of the country which enable this nation a strong social capital possession in building superior civilization. In reality, however, such lofty values of national cultures, experiencing many challenges, due to the rush out of external values and step in the original values of our national cultures. Local wisdoms in many groups of / minority communities in Indonesia have been often overlooked, whereas, these local wisdoms can actually be promoted to become a model for developing the character education-based on Indonesia’s character of origins. By the use of cultural-anthropology approach, this paper tries to uncover local wisdom values on indigenous Bedouin people of Banten as a defining characters, i.e. environmental care, love to work hard, obedient to law /customary law, a simplicity /independent, democratic, hard-working and uphold honesty. These values, in line with author’s research findings actually to be internalized and preserved among indigenous peoples, to be taught, socialized, exemplified and enforced strictly by the rules, so as to form a strong character.